PENGARUH MODEL PEMBELAJARAN TIPE NUMBER HEAD TOGETHER DAN METODE CERAMAH TERHADAP HASIL BELAJAR KELAS XI PADA MATA PELAJARAN AKUNTANSI DI SMANEGERI 6 KOTA JAMBI - Pratiwi Indah Sari (Universitas Batanghari Jambi, 2016)
The purpose of this research is to describe the extent of the influence and relationship-type learning model number head together and lecture method terhaadap learning outcomes xi classes in accounting subjects in SMAN 6 Jambi. Design of this study using an experimental research approach, the sample in this study amounted to 83 students in SMAN 6 Jambi. with a data-processing technique using the formula average. The results showed that the learning outcomes of students in the control classes using methods lectures on the subjects of Accounting at SMAN 6 Jambi are in scores of 87.5. The results of students in class experiments using model types Number Head Together on the subjects of Accounting at SMAN 6 Jambi currently on scores 92.5. Judging from the comparison the control class that is 87.5> 92.5 with a difference of 5.0 points in the experimental class. Thus, it can be concluded that the use of NHT method was found to increase student learning outcomes in accounting subjects in SMAN 6 Jambi.Keyword : Number Head Together, Methods of Teaching, Learning Outcomes